Relationship Between the ApaI (rs7975232), BsmI (rs1544410), FokI (rs2228570), and TaqI (rs731236) Variants in the Vitamin D Receptor Gene and Urolithiasis Susceptibility: An Updated Meta-Analysis and Trial Sequential Analysis - Chen, Guangyuan; Hu, Cong; Song, Yuxuan; Xiu, Mengxi; Liang, Wanfeng; Ou, Ningjing; Liu, Xiaoqiang; Huang, Peng (Frontiers in Genetics, 2020)
The relationship between urolithiasis and vitamin D receptor (VDR) gene variants is still under debate according to the available published literature. To assess correlations between VDR gene variants ApaI (rs7975232), BsmI (rs1544410), FokI (rs2228570), and TaqI (rs731236) and urolithiasis susceptibility, we performed the present study through meta-analysis. The PubMed, Cochrane Library, China National Knowledge Infrastructure, EMBASE, Web of Science, and Wanfang databases were searched to retrieve qualified case-control studies. Finally, 31 reports were selected for the present meta-analysis. The results demonstrated that the VDR gene TaqI TT genotype was related to decreased risk of urolithiasis in the overall population (TT vs. Tt+tt: P = 0.011, OR = 0.824, 95% CI = 0.709–0.957). In ethnicity subgroup analysis, we found that the TaqI variant was obviously correlated to urolithiasis risk among Asians and Caucasians (P < 0.05). Additionally, significant urolithiasis risk was identified in adults. However, the FokI, BsmI, and ApaI variants did not have an increased risk of developing urolithiasis. Trial sequential analysis results were on a sufficiently large number of participants and did not require more research to confirm associations. Our research suggested that the VDR gene variant TaqI was correlated with urolithiasis susceptibility and that the t-allele might be the risk gene and T-allele the protective gene in VDR TaqI variant.